Modeling the Workpiece Heating on a Plasma Nitriding Equipment Using Neural Networks. (2015) - Oltean, Stelian-Emilian
Abstract: The plasma nitriding is a complex process which contains many variables and inter-influences and it is applied on different workpieces to improve the surface properties. Knowing the process characteristics and obtaining the model of the process is an important stage in future design of the equipment control system. Based on the observed behavior of the system and using some experimental data from different nitriding processes it was proposed in this paper a neural network model for the workpiece heating effect. The final structure of the neural network model has one hidden layer, the workpiece temperature as output and was implemented and tested in the Matlab/Simulink environment.